THE UTILIZATION OF AUGMENTED REALITY TECHNOLOGY IN DETERMINING QIBLA DIRECTION (ANALYSIS OF MIQAT APPLICATIONS BY SAMER JOUDI) - Muttaqin, Naufal Fazal (Al-Hilal: Journal of Islamic Astronomy, 2023)
Nowadays, around the world, there are numerous Qibla direction applications available on various websites and digital content providers. One of these is the Miqat application: Prayer Times, Qiblah, and Hilal Visibility, an augmented reality-based Android app for determining the direction of the Qibla. Samer Joudi, a geospatial technology specialist from the United Arab Emirates, released the Miqat app in 2015. As of November 20, 2022, more than 5,000,000 (five million) Android users had downloaded the Miqat app, giving it a rating of 4.6 out of 5. A 3D Qibla feature in the Miqat application uses augmented reality technology on the display to point users in the direction of the Kaaba. actual life.  The results of this study are that the calculation method used by the Miqat application is the Vincenty formula, which is quite accurate (7 minutes difference from the calculation of the Istiwa'aini Qibla direction) because the Vincenty formula has high accuracy in determining the Qibla direction based on the ellipsoid shape of the earth. Then, determining the Qibla direction using the 3D Qibla feature with augmented reality technology is categorized as less accurate according to Slamet Hambali's level of accuracy, but still within tolerance limits according to Thomas Djamaluddin's level of accuracy. The accuracy of the Qibla direction of the Miqat application differs from 0o to 1o from the Qibla direction measured by Istiwa'aini.